Democratization and civilian control in Asia - Chambers, Paul W. (Critical Studies of the Asia-Pacific, 2013)
Cover; Contents; List of Illustrations; Acknowledgments; List of Abbreviations; Introduction; Part I: Conceptual and Theoretical Perspectives; 1 Conceptualizing Civilian Control of the Military; 2 Explaining Civilian Control of the Military in New Democracies; Part II: Democratization and Civil-Military Relations in Asia; 3 South Korea: Purges and Presidential Prerogatives; 4 Taiwan: From Martial Law to Civilian Control; 5 Indonesia: The Democratization of Personal Control; 6 Bangladesh: From Militarized Politics to Politicized Military